Do Patient-derived Spheroid Culture Models Have Relevance in Chondrosarcoma Research?. Issue 3 (March 2021) - Ma, Ruichen; Mandell, Jonathan; Lu, Feiqi; Heim, Tanya; Schoedel, Karen; Duensing, Anette; Watters, Rebecca J.; Weiss, Kurt R.
Abstract: Background: In high-grade chondrosarcoma, 5-year survival is lower than 50%. Therefore, it is important that preclinical models that mimic the disease with the greatest possible fidelity are used to potentially develop new treatments. Accumulating evidence suggests that two-dimensional (2-D) cell culture may not accurately represent the tumor's biology. It has been demonstrated in other cancers that three-dimensional (3-D) cancer cell spheroids may recapitulate tumor biology and response to treatment with greater fidelity than traditional 2-D techniques. To our knowledge, the formation of patient-derived chondrosarcoma spheroids has not been described. Questions/purposes: (1) Can patient-derived chondrosarcoma spheroids be produced? (2) Do spheroids recapitulate human chondrosarcoma better than 2-D cultures, both morphologically and molecularly? (3) Can chondrosarcoma spheroids provide an accurate model to test novel treatments? Methods: Experiments to test the feasibility of spheroid formation of chondrosarcoma cells were performed using HT-1080, an established chondrosarcoma cell line, and two patient-derived populations, TP19-S26 and TP19-S115. Cells were cultured in flasks, trypsinized, and seeded into 96-well ultra-low attachment plates with culture media. After spheroids formed, they were monitored daily by bright-field microscopy. Spheroids were fixed using paraformaldehyde and embedded in agarose. After dehydration with isopropanol, paraffin-embedded spheroids were sectioned, and slides were stained with hematoxylin and eosin. To compare differences and similarities in gene expression between 2-D and 3-D chondrosarcoma cultures and primary tumors, and to determine whether these spheroids recapitulated the biology of chondrosarcoma, RNA was extracted from 2-D cultures, spheroids, and tumors. Quantitative polymerase chain reaction was performed to detect chondrosarcoma markers of interest, including vascular endothelial growth factor alpha, hypoxia-inducible factor 1α, COL2A1, and COL10A1. To determine whether 2-D and 3-D cultures responded differently to novel chondrosarcoma treatments, we compared their sensitivities to disulfiram and copper chloride treatment. To test their sensitivity to disulfiram and copper chloride treatment, 10, 000 cells were seeded into 96-well plates for 2-D culturing and 3000 cells in each well for 3-D culturing. After treating the cells with disulfiram and copper for 48 hours, we detected cell viability using quantitative presto-blue staining and measured via plate reader. Results: Cell-line and patient-derived spheroids were cultured and monitored over 12 days. Qualitatively, we observed that HT-1080 demonstrated unlimited growth, while TP19-S26 and TP19-S115 contracted during culturing relative to their initial size. Hematoxylin and eosin staining of HT-1080 spheroids revealed that cell-cell attachments were more pronounced at the periphery of the spheroid structure than at the core, while the core was less dense. Spheroids derived from the intermediate-grade chondrosarcoma TP19-S26 were abundant in extracellular matrix, and spheroids derived from the dedifferentiated chondrosarcoma TP19-S115 had a higher cellularity and heterogeneity with spindle cells at the periphery. In the HT-1080 cells, differences in gene expression were appreciated with spheroids demonstrating greater expressions of VEGF-α (1.01 ± 0.16 versus 6.48 ± 0.55; p = 0.003), COL2A1 (1.00 ± 0.10 versus 7.46 ± 2.52; p < 0.001), and COL10A1 (1.01 ± 0.19 versus 22.53 ± 4.91; p < 0.001). Differences in gene expressions were also noted between primary tumors, spheroids, and 2-D cultures in the patient-derived samples TP19-S26 and TP19-S115. TP19-S26 is an intermediate-grade chondrosarcoma. With the numbers we had, we could not detect a difference in VEGF-α and HIF1α gene expression compared with the primary tumor. COL2A1 (1.00 ± 0.14 versus 1.76 ± 0.10 versus 335.66 ± 31.13) and COL10A1 (1.06 ± 0.378 versus 5.98 ± 0.45 versus 138.82 ± 23.4) expressions were both greater in the tumor (p (COL2A1) < 0.001; p (COL10A1) < 0.0001) and 3-D cultures (p (COL2A1) = 0.004; p (COL10A1) < 0.0001) compared with 2-D cultures. We could not demonstrate a difference in VEGF-α and HIF1α expressions in TP19-S115, a dedifferentiated chondrosarcoma, in the tumor compared with 2-D and 3-D cultures. COL2A1 (1.00 ± 0.02 versus 1.86 ± 0.18 versus 2.95 ± 0.56) and COL10A1 (1.00 ± 0.03 versus 5.52 ± 0.66 versus 3.79 ± 0.36) expressions were both greater in spheroids (p (COL2A1) = 0.003; p (COL10A1) < 0.0001) and tumors (p (COL2A1) < 0.001; p (COL10A1) < 0.0001) compared with 2-D cultures. Disulfiram-copper chloride treatment demonstrated high cytotoxicity in HT-1080 and SW-1353 chondrosarcoma cells grown in the 2-D monolayer, but 3-D spheroids were highly resistant to this treatment. Conclusion: We provide preliminary findings that it is possible to generate 3-D spheroids from chondrosarcoma cell lines and two human chondrosarcomas (one dedifferentiated chondrosarcoma and one intermediate-grade chondrosarcoma). Chondrosarcoma spheroids derived from human tumors demonstrated morphology more reminiscent of primary tumors than cells grown in 2-D culture. Spheroids displayed similar expressions of cartilage markers as the primary tumor, and we observed a higher expression of collagen markers in the spheroids compared with cells grown in monolayer. Spheroids also demonstrated greater chemotherapy resistance than monolayer cells, but more patient-derived spheroids are needed to further conclude that 3-D cultures may mimic the chemoresistance that chondrosarcomas demonstrate clinically. Additional studies on patient-derived chondrosarcoma spheroids are warranted. Clinical Relevance: Chondrosarcomas demonstrate resistance to chemotherapy and radiation, and we believe that if they can be replicated, models such as 3-D spheroids may provide a method to test novel treatments for human chondrosarcoma. Additional comprehensive genomic studies are required to compare 2-D and 3-D models with the primary tumor to determine the most effective way to study this disease in vitro.